Research on influential factors of crack propagation depth of unsaturated residual soils under short-term variations in external air pressure - Xu-tang Xu; Wen-bin Jian; Ye-qing Cai; Xiang-long Chen (Geomatics, Natural Hazards & Risk)
The presence of cracks significantly influences the engineering properties of unsaturated residual soil, particularly under external air pressure fluctuation (i.e. Δua). A formula is developed that integrates existing crack depth theories with factors such as soil shear strengths, effective stress parameters, effective tensile strength reduction coefficients, and environmental changes like infiltration and evaporation. In addition, a further equation is deduced to determine the surface flow rate cracking value Q0, which can reflect the influence of seasonal climate on the matric suction of the surface soil. Our findings reveal that crack depth is quite reactive to short-term fluctuations in external air pressure, effective stress parameters and evaporation intensity, with remarkable increases in crack depth linked to these variations. The theoretical depth of soil crack increases by 0.12 ∼ 0.27m when the external air pressure fluctuation (i.e. Δua) is 3 kPa. Soils subjected to climatic conditions crack only when Q>Q0, and early cracking of soils under Δua>0 is conditioned by increasing infiltration and effective cohesion or reducing evaporation. The variation rule of the theoretical crack depth calculated in this research shows consistency with the previous equations, and the model predictions at Δua = 3kPa are proved to match well with the measured results of the practical engineering subjected to various climate environment factors.